SiC 기반 3-레벨 NPC 인버터의 전력 손실 프로파일 및 접합 온도 추정 - 이인호 (The Graduate School, Ajou University, 2024)
This thesis presents a power loss profile and junction temperature estimation method for SiC-based power semiconductor devices in a three-level neutral point clamped (NPC) inverter. Thermal analysis of the power devices is essential for enhancing the reliability of power conversion systems (PCSs) since excessive temperature rise in devices can lead to failures such as thermal degradation or material distortion. The power loss is determined by the switching states, which are controlled as the inverter operates. This power loss is subsequently spread out into the form of thermal energy through materials within the power transfer path, including die, thermal interface material (TIM), and heat sink. Thermal equivalent circuit analysis is utilized to estimate the junction temperature variation caused by the power loss to model this phenomenon. In this paper, a power loss profile of SiC-based power devices in three-level NPC inverters is designed and the power loss is converted into thermal behavior using an RC thermal network model to estimate the junction temperature. The thermal model reflects the physical characteristics of the power devices. The validity of the junction temperature estimation method was verified through simulation and experimental results.
학위논문(석사)--전자공학과,2024. 2
Keywords: 3-level NPC inverter; Junction temperature; Power loss; SiC MOSFET